Circular Airport Concept Analysis for Indonesian Archipelago - Kusumalestari, A S; Franciscus, F (International Journal of Aviation Science and Engineering - AVIA, 2021)
Circular Airport Concept, issued by Hessellink in 2014, divides the expert opinion, but the project is still running. The idea is how visible to engage this concept into Indonesian Archipelago. To build airport within limit area for several islands in Indonesia is a big challenge. Some pioneer routes which connecting remote areas with a small aircraft is still searching for some development. Another challenge is the environmental sustainability. This paper makes an analysis about application of the concept into Indonesian Archipelago, and how this concept might be a solution. The discussion will cover analysis of airport design, aircraft to operate, and area to be treated.